Analysis of the Feasibility of Ground Support Equipment (GSE) Relationship Analysis of PT. Gapura Angkasa on the Performance of Ground Support Operators at Bandung's Husein Sastranegara International Airport - Alif Muhammad Firdaus; Yunus Purnama (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effect of GSE feasibility on the performance of GSE operator PT. Gapura Angkasa at Husein Sastranegara International Airport Bandung. This study used a quantitative method with data collection techniques through questionnaires and documentation. The respondents of this research are all employees of PT. Gapura Angkasa Bandung. Testing the data from this study used a statistical descriptive test and a simple linear regression test using IBM SPSS 25 Statistics for Windows. The results of the study show that the influence of variable X (feasibility) on variable Y (performance) of GSE operator employees shows strong results by obtaining a correlation coefficient of 0.637 and a coefficient of determination of 40.6% with the remaining 59.4% being influenced by factors others that were not examined by researchers.